Case Study of Rose Water Antioxidant Activities with Variations of Filtering Methods: Studi Kasus Aktivitas Antioksidan Air Mawar Dengan Variasi Metode Penyulingan - Erviana Angga Yulia Dari; Yannie Asrie Widanti; Akhmad Mustofa (Fakultas Sains dan Teknologi Unisri, 2024)
Red roses (Rosa damascena Mill) are a type of rose with a distinct aroma and a deep red color. Roses are usually used as decoration, but it also has health benefits. Roses have bioactive compounds and anthocyanin pigments that act as antioxidants. The expected outcome of this research is to produce rose water products that have a strong aroma and have high antioxidant activity. This study used a factorial Completely Randomized Block Design (RAKL) method. The factor used is the variation of the distillation method. While the length of the extraction process was used as the sampling time. The correct distillation method to produce rose water which has high antioxidant activity is treatment with variations of the steam distillation method. The steam distillation method obtained the following results: pH 4.07, vitamin C content 40.70 mg/100g, total phenol content 47.10 mg GAE/g, antioxidant activity of DPPH 64.20%, FRAP value 98.97% and sensory test (scent) 3.34.